Mild Cold Exposure Modulates Fibroblast Growth Factor 21 (FGF21) Diurnal Rhythm in Humans: Relationship between FGF21 Levels, Lipolysis, and Cold-Induced Thermogenesis - Lee, Paul; Brychta, Robert J.; Linderman, Joyce; Smith, Sheila; Chen, Kong Y.; Celi, Francesco S. (The journal of clinical endocrinology and metabolism, 2013)
Context:Cold exposure stimulates fibroblast growth factor 21 (FGF21) secretion in animals, enhancing the cold-induced thermogenesis (CIT) response through browning of white adipose tissue. In humans, the effects of cold exposure on circulating FGF21 levels are unknown.Objective:Our objective was to evaluate the effects of mild cold exposure on circulating FGF21 and its relationship with CIT and lipolysis in humans.Design and Setting:We conducted a randomized, single-blind, crossover intervention study at the National Institutes of Health Clinical Center.Participants:Participants were healthy adults.Intervention:Subjects were exposed to a 12-h exposure to 24 or 19 C in a whole-room indirect calorimeter.Outcome Measures:Energy expenditure, plasma FGF 21, nonesterified fatty acid, and adipose tissue microdialysis glycerol concentrations were evaluated.Results:At 24 C, plasma FGF21 exhibited a diurnal rhythm, peaking at 0800 h [110 (59–178) pg/ml], and progressively dropped to a nadir at 1700 h [41 (21–71) pg/ml, P < 0.0001] before rising at 1900 h [60 (11–81) pg/ml, P < 0.0001]. Exposure at 19 C lessened the diurnal reduction of FGF21 observed at 24 C from 0800–1700 h and augmented overall FGF21 levels by 37 ± 45% (P = 0.01). The change in area under the curve plasma FGF21 between 19 and 24 C correlated positively with the change in area under the curve adipose microdialysate glycerol (R2 = 0.35, P = 0.04) but not with nonesterified fatty acid. Cold-induced increase in FGF21 predicted greater rise in energy expenditure during cold exposure (β = 0.66, P = 0.027), independent of age, gender, fat mass, and lean mass.Conclusions:Mild cold exposure increased circulating FGF21 levels, predicting greater lipolysis and CIT. A small reduction in environmental temperature is sufficient to modulate FGF21 diurnal rhythm in humans, which may mediate cold-induced metabolic changes similar to those in animals.